Pemberdayaan Siswa melalui Kampanye Anti-Bullying berbasis Nilai Sportivitas dalam Pendidikan Jasmani - haryo mukti; Septyaningrum Putri Purwoto; Ihwan Firmansyah; Asroful Anam; Alfi Raudatul Fadillah (JA (Jurnal Abdiku) : Jurnal Pengabdian Kepada Masyarakat, 2026)
The development of digital technology has made it easier for students to access information and communicate; however, it has also presented challenges in the form of increasing risks of bullying and cyberbullying in school environments. Low levels of digital literacy and a lack of understanding of social media ethics are among the factors that may trigger bullying among adolescents. This community service activity aimed to improve students’ understanding of bullying prevention through the use of digital media integrated with the values of physical education. The activity was conducted on May 12, 2026, from 09:00 to 12:00 WIB at the Hall of SMP Negeri 5 Bangkalan. The implementation method employed a socialization approach through the delivery of educational materials, the screening of educational videos, interactive discussions, and an evaluation of participants’ understanding. The materials covered the concepts of bullying and cyberbullying, the negative impacts of bullying behavior, ethical digital media use, and the reinforcement of sportsmanship, empathy, cooperation, and mutual respect in school life. The results showed that participants demonstrated good enthusiasm throughout the socialization process and experienced an improvement in their understanding of various forms of bullying, the negative impacts of bullying, and the importance of using digital media positively and responsibly. The integration of physical education and digital literacy represents a relevant approach to developing students’ social character and supporting the creation of a safe and inclusive school environment. This activity is expected to serve as an initial step for schools in developing sustainable educational programs related to bullying prevention and character development through the use of digital technology.